Perancangan Rumah Batik Banyuwangi dengan Pendekatan Placemaking oleh Konsultan Arsitektur Interior [V]Atelier - Anastasha, Veronica; Susan, Susan (KREASI, 2024)
Humans require locations that can serve as facilities and infrastructure to carry out their daily lives. Of course, this demonstrates the significance of an architect or interior designer in creating a space that meets the requirements of its users. It is determined from the completed analysis of the business environment that there is a growing demand for commercial property at the time. It might present an opportunity for [V]Atelier, a commercial interior architectural consultant, to provide a placemaking strategy for commercial spaces. The Banyuwangi Batik House design project is an implementation project in describing business innovation and value [V]Atelier is present as a commercial interior architecture consultant that offers a design approach to placemaking. To create a warm and comfortable interior, the Banyuwangi Batik House’s design will incorporate aspects of the Banyuwangi Batik culture. In its design, Rumah Batik Banyuwangi raised the concept of "batik stories" which can provide a comprehensive picture of the characteristics of Banyuwangi batik as one of Banyuwangi’s proud cultures. Designing the "batik story" idea will involve applying the creative placemaking approach, which incorporates aspects of Banyuwangi batik culture and art. Rumah Batik Banyuwangi is hoping that by putting this idea into practice, it will enable all tiers of Banyuwangi society to live fulfilling lives by instilling values in each of the attributes that Banyuwangi batik presents.